Getting into the zone: how the internet of things can improve energy efficiency and demand response in a commercial building - Peng Zhao; Therese Peffer; Ram Narayanamurthy; Gabe Fierro; Paul Raftery; Soazig Kaam; Joyce Kim (2016 ACEE Summer Study on Energy Efficiency in Buildings, 2016)
While building automation and controls have long used data and analytics to improve building performance, the proliferation of connected devices and sensors adds a new dimension with greater insight to the end user’s impact on energy consumption. The application of the Internet of Things (IoT) in building systems allows connected devices to communicate and provide enhanced control functions. The increasingly improved visibility at the zonal/room level suggests several ways to improve both energy efficiency and demand response. UC Berkeley researchers have worked to interface wireless networks with existing building automation systems (BAS) as well as creating virtual BASs by interconnecting control and sensor hardware. The simple Monitoring and Actuation Profile (sMAP) delivers and labels data from various sources into a single compact database; the eXtensible Building Operating System (XBOS) provides the platform for applications to access this data. This paper describes a collaborative research project between Electric Power Research Institute (EPRI) and UC Berkeley that builds on this work by examining data from several sources: the BAS of a commercial building on campus, wireless indoor environmental sensors (temperature, light, humidity, motion, carbon dioxide), browser-based thermal comfort voting, a networked heated-and-cooled chair, and connected plugload sensors. We describe the results of testing the individual tools, and next steps.